Developing Nuclear Security Culture at Academic and Educational Institutions - Mostafa Kofi; Lamiaa Fiala; May Al-Muammar; Zenobia S Homan (International Journal of Nuclear Security, 2020)
In recent years, the use of radioactive and nuclear sources for diagnosis and treatment has become more widespread in the medical field. These sources are present in universities, university hospitals, and academic institutions, making it necessary to develop a strong nuclear security culture among academics. There are many widespread and complex challenges to improving security culture, often from scratch. The research solution presented in this paper is how to develop a strong and sustainable nuclear security culture among academics. Workplaces are often culturally diverse, so it can be challenging to achieve a common belief in nuclear security and an institutional commitment to upholding such standards. Researchers have identified obstacles, such as English language barriers, a sufficient commitment from management to develop a strong security culture, the ability to make use of innovative educational resources, and defining a clear nuclear security policy for the institutions in question. Analysis of these issues indicates that there is a need for nuclear security to be implemented more clearly from internal roles and regulations rather than being imposed as an external requirement.
Keywords: nuclear security; culture; universities; academics